Bio-diversity ride for Khazanah Alam Mountain Bike Jamboree online registration system / Nor Zalina Ismail … [et al.] - Ismail, Nor Zalina; Razak, Mohd. Rizal; Abd. Aziz, Muhd. Eizan Shafiq; Zolkefley, Mohd Khairul Ikhwan; Wan Abdul Rahman, Wan Mohd Nazri (2015)
Bio-Diversity Ride for Khazanah Alam Mountain Bike Jamboree or also known as Khazanah Alam Jamboree was conducted to celebrate 30 years of Universiti Teknologi MARA Pahang. Due to the Information Technology growth, the registration system for this event was done using on-line registration system. This online registration system replaces the existing manual registration procedure that has many drawbacks. Manual registration system used paper forms and sometimes phone calls or e-mails. The issues that always occur when using manual registration system are data redundancy, data loss, difficulty to estimate the number of participants and groups and difficulty to estimate the number of t-shirts to be ordered. The objectives of this system were to simplify the registration and payment process. Another objective was to reduce problems occuring when using the manual registration system. The method used to develop this system was Dynamic System Development Method (DSDM) that has five main processes. This system had three types of users which were system moderator, riders and public. This system reduced time and procedure for registration and payment process. It gave a lot of benefits for committees, riders and public.